Polyacrylic Acid Functionalized Nanographene as a Nanocarrier for Loading and Controlled Release of Doxorubicin Hydrochloride. (9th September 2013) - Chen, Yunping; Qi, Yuanyuan; Liu, Bin
Abstract : Graphene nanosheets (GNSs) were synthesized by direct current arc discharge and subsequently functionalized by highly hydrophilic polyacrylic acid (PAA). The loading and release of doxorubicin hydrochloride (DOX) on PAA-functionalized GNSs (PAA-GNSs) were investigated. PAA-GNSs were successfully prepared and verified by atomic force microscope (AFM), Fourier-transform infrared (FTIR) and ultraviolet-visible (UV-vis) spectroscopes, and thermogravimetric analysis (TGA). The PAA-GNSs contained about 10 wt% PAA which significantly improved the solubility of GNSs in aqueous media. The efficient loading of DOX onto the PAA-GNSs is as high as 2.404 ± 0.167 mg/mg at the DOX concentration of 0.36 mg/mL. Furthermore, the PPA-GNSs showed strong pH-dependent behavior and efficient slow release ability. Therefore, PAA-GNSs are promising new materials for biological and medical applications.